Freeing the world of chemical weapons: The Chemical Weapons Convention at the ten-year-mark - Oliver Thränert; Jonathan B. Tucker (Stiftung Wissenschaft und Politik (SWP), 2007)
The Chemical Weapons Convention (CWC) is the first multilateral arms control treaty to prohibit an entire category of unconventional arms in a verifiable manner and the only such agreement to have a dedicated implementing body, the Organization for the Prohibition of Chemical Weapons (OPCW). The tenth anniversary of the CWC's entry into force, which took place on 29 April 2007, provides an opportune moment to assess the treaty's implementation and to recommend improvements. This study seeks to answer two questions: What has been accomplished since the CWC entered into force? And what are the main problems that remain to be solved? The paper includes discussions and recommendations on key issues such as Universality; Destruction of Chemical Weapons; Verification of Compliance; International Cooperation and Assistance; and the Second Review Conference that has been scheduled for April 2008. (SWP Research Papers)
Keywords: 320